Covert Operations Unveiling Organized Crime : using operation Donnie Brasco to understand the complex trauma of deep cover - Rudofossi, Daniel, 1961- (New York and London: Routledge, Taylor & Francis, 2023)
"NYPD "Cop Doc" Dr. Dan Rudofossi delves into what it meant to live as a deep-cover operative through narratives with Joe Pistone, the FBI agent who spent six years living as Donnie Brasco as a member of the Bonanno crime family. When Operation Donnie Brasco abruptly closed, it was the longest and most successful infiltration of a Mafia family. Dr. Rudofossi underscores Pistone's genius to survive daily challenges of infiltration by using innovations in the ecological niches of Mafia violence. Donnie Brasco's "mental toughness," resilience, and ingenuity are understood through Rudofossi's signature eco-ethological existential analysis: Mapping out why and how trauma shaped functional dissociation as unconscious adaptation, the author's experience as a police psychologist-that is, a "cop doc"-helps decode the bigger picture of conflict, resolution, and compromise in the disparate worlds of policing and organized crime. This unique look at the costs and successes of tracking, infiltrating, arresting, and convicting those involved in organized crime is a groundbreaking read for law enforcement personnel, criminal justice, homeland security, law students, police psychologists, as well as anyone fascinated by the world of organized crime"
Includes bibliographical references and index.
Keywords: Organized crime; Undercover operations; Police psychology